Training of Future Elementary School Teachers to Usage of the Communicative Strategies in Multi Ethnic Environment in Mountain Region Schools - Oliyar, Mariya (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article characterizes the main aspects of language-related policy in Ukraine. It explores the leading role of elementary school teacher in the consolidation of statehood of Ukrainian language in the mountain region of Ukrainian Carpathians. It analyzes the latest research and publications on the problem of training of future elementary school teachers in use of communication strategies in a poly-ethnic environment of school in the mountain region. The article also defines the most important tendencies that influence a professional-communicative activity of the teacher in a mountain region. It explores the specifics of professional activity of the elementary school teacher in the mountain region schools of Ukrainian Carpathians. It also characterizes the problems encountered by a teacher at his work. The article describes the peculiarities of training of future teachers in communicative-strategic activity in the mountain school region. It also defines the trends of professional training of students planning to work in the mountain region environment, that are not outlined in the existing curricula and study programs. Finally, the article uncovers the concept of ethic-pedagogic approach to the linguistic education of children in mountain region schools, as well as formulates the conclusions and defines the guidelines for further research.